Evaluating bionanoparticle infused fungal metabolites as a novel antimicrobial agent - Kartikeya Rajpal; Nafe Aziz; Ram Prasad; Ramendra G Varma; Ajit Varma (Wolters Kluwer Medknow Publications, 2016)
Therapeutic properties of fungal metabolites and silver nanoparticles have been well documented. While fungal metabolites have been used for centuries as medicinal drugs, potential of biogenic silver nanoparticles has recently received attention. We have evaluated the antimicrobial potential of Aspergillus terreus crude extract, silver nanoparticles and an amalgamation of both against four pathogenic bacterial strains. Antimicrobial activity of the following was evaluated - A. terreus extract, biogenic silver nanoparticles, and a mixture containing extract and nanoparticles. Four pathogenic bacteria - Klebsiella pneumoniae, Escherichia coli, Staphylococcus aureus, and Bacillus cereus were used as test organisms. Phenol, flavonoid, and alkaloid content of extract were determined to understand the chemical profile of the fungus. The extract contained significantly high amounts of phenols, flavonoids, and alkaloids. The extract and biogenic silver nanoparticle exhibited significant antibacterial activity at concentrations of 10 μg/ml and 1 μg/ml, respectively. When used in combination, the extract-nanoparticle mixture showed equally potent antibacterial activity at a much lower concentration of 2.5 μg/ml extract + 0.5 μg/ml nanoparticle. Given its high antibacterial potential, the fungal extract can be a promising source of novel drug lead compounds. The extract - silver nanoparticle mixture exhibited synergism in their antibacterial efficacy. This property can be further used to formulate new age drugs.